التربية والفلسفة التربوية من منطلق وظيفي - فرحات,فريدة (University of Eloued جامعة الوادي, 2023)
ملخص: الأزمة التربوية من بين عديد الأزمات العالقة والتي هي حيز الطرح و المعالجة في الفكر العربي المعاصر، لأهميتها المنبثقة من الموضوع الذي تتناوله و الوظيفة التي تؤديها وتكمن في إعداد الناشئة و تحقيق نمائها عبر العضوية الإجتماعية التي تختص بالتميز بالماهية الثقافية، ولأن هذا الفرد هو العنصر الأساسي في تطور المجتمعات وبناء الحضارات وصنعها بفاعلة الذات، بات من الضروري بمكان الإهتمام به في الدراسات التربوية والأطاريح الفلسفية ،وعليه فإن الإشكالية التي يترتب علنا إثارتها كيف يمكن التكامل الوظيفي بين الفعل الفلسفي و الفعل التربوي في عملية تأهيل الفرد والإرتقاء به لصفة المواطنة ولإكتمال بنيته الإجتماعية؟ و ماهي السبل التربوية والفلسفية الكفيلة بتحقيق تجاوز الفرد لذاته و لآليات عجزه أمام عديد العوائق الإبستيمية التي تعترض مساره أثناء قيامه بوظيفته الإجتماعية؟ و ما قيمة فلسفة الفعل في العملية التربوية؟ . Abstract: he educational crisis is one of many pressing issues that are the subject of discussion and examination in contemporary Arab thought. Its importance arises from the topic it addresses and the role it plays, which lies in preparing and nurturing the younger generation through the social organicity specialized in cultural excellence. Since the individual is the fundamental element in the development of societies, the construction of civilizations, and their self-empowerment, it has become imperative to focus on this individual in educational studies and philosophical frameworks. Therefore, the fundamental question that needs to be addressed is how functional integration can be achieved between philosophical action and educational action in the process of individual development and the enhancement of their citizenship and social structure. What are the educational and philosophical means capable of enabling the individual to surpass themselves and the mechanisms of their inadequacy in the face of numerous systemic obstacles encountered during the fulfillment of their social role? What is the value of the philosophy of action in the educational process?
Keywords: الفكر العربي المعاصر; المواطنة; الفعل الفلسفي; Educational Crisis; Contemporary Arab Though; SOCIAL SCIENCES::Social sciences::Education; Philosophical Action; Citizenship; Educational Process